2020
DOI: 10.3892/or.2020.7459
|View full text |Cite
|
Sign up to set email alerts
|

Cyclovirobuxine D inhibits cell proliferation and migration and induces apoptosis in human glioblastoma multiforme and low‑grade glioma

Abstract: Gliomas are the most common neoplasm of the human central nervous system. Glioblastoma multiforme (GBM) is one of the most serious types of gliomas. Although considerable progress has been made in the development of cancer therapeutic agents, several antineoplastic drugs fail to penetrate the blood-brain barrier (BBB), resulting in a low survival rate of glioma patients. Recent studies have revealed that the traditional Chinese medicine Buxus microphylla contains the main active component Cyclovirobuxine D (CV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Our study shows that CVB-D effectively and long-lastingly relieves PTX-induced thermal hypersensitivity ( Figure 8 ). This finding, in conjunction with recent reports of CVB-D’s promising in vitro and in vivo antiproliferative activities ( Wu et al, 2015 ; Jiang et al, 2020 ; Zhang et al, 2020 ; Zhou et al, 2020 ; Liu et al, 2021 ; Zeng et al, 2021 ), also raises the potential of an application of CVB-D in cancer treatment and chemotherapy: a combination of CVB-D and PTX may offer a promising opportunity to concurrently enhance the anticancer effect of PTX and reduce its unwanted neuropathic symptoms.…”
Section: Discussionmentioning
confidence: 58%
“…Our study shows that CVB-D effectively and long-lastingly relieves PTX-induced thermal hypersensitivity ( Figure 8 ). This finding, in conjunction with recent reports of CVB-D’s promising in vitro and in vivo antiproliferative activities ( Wu et al, 2015 ; Jiang et al, 2020 ; Zhang et al, 2020 ; Zhou et al, 2020 ; Liu et al, 2021 ; Zeng et al, 2021 ), also raises the potential of an application of CVB-D in cancer treatment and chemotherapy: a combination of CVB-D and PTX may offer a promising opportunity to concurrently enhance the anticancer effect of PTX and reduce its unwanted neuropathic symptoms.…”
Section: Discussionmentioning
confidence: 58%
“…However, the more detailed mechanism of cyclovirobuxine D to treat LGG has not been investigated. 52 In our study, we screened multi‐TCM databases and identified gallic acid as a novel potential RAB13 inhibitor, which was confirmed to negatively regulate autophagy as well as to induce cell death in SW1088 cells. Our study offers a new candidate TCM compound, gallic acid, to treat LGG with detailed mechanism—by inhibiting RAB13 and suppressing autophagy.…”
Section: Discussionmentioning
confidence: 90%
“…Recently, TCM cyclovirobuxine D, derived from Buxus microphylla, was reported to possess therapeutic potential on LGG through blocking cell cycle and activating apoptosis. However, the more detailed mechanism of cyclovirobuxine D to treat LGG has not been investigated 52 . In our study, we screened multi‐TCM databases and identified gallic acid as a novel potential RAB13 inhibitor, which was confirmed to negatively regulate autophagy as well as to induce cell death in SW1088 cells.…”
Section: Discussionmentioning
confidence: 95%
“…Cyclovirobuxine D (CVB‐D) is the major active component of Buxus microphylla, which is mainly used in the treatment of cardiovascular and cerebrovascular diseases (Bian et al, 2021; Yu, Fang, Lü, Xu, & Lu, 2011). In recent years, more and more evidence has suggested that CVB‐D may have inhibitory effects on various tumors (Lu et al, 2014; Zeng et al, 2021; Zhou et al, 2020). Besides, CVB‐D inhibits CRC cell growth and decreases angiogenesis via the CTHRC1‐AKT/ERK‐Snail signaling pathway, especially microvasculature (Jiang et al, 2020).…”
Section: Natural Anti‐gic Angiogenic Compounds Derived From Plantsmentioning
confidence: 99%